The Effect of Service Quality on Customer Satisfaction in JKT48 Theater - Rahayu, Nurti; Prasetia, Rakaputra; Priyanto, Priyanto (Institut Pariwisata Trisakti, 2019)
The purpose of the research was to identify the influence of service quality on the customer satisfaction in JKT48 Theater, such as tangibles, reliability, responsiveness, assurance, empathy. This research was descriptive research. Data collection techniques used in data collection in this study were observations, questionnaires, and interviews conducted in November 2018 untill December 2018. While the method used for data analysis is to test the validity, reliability, correlation, and coefficient of determination. Based on the correlational test results it is known that the correlation between service quality and customer satisfaction produces 0.809 or 80.9% which can be categorized as having a very strong relationship. Based on the results of the test of determination coefficient it is known that the value of R Square is 0.655 which means that the variable quality of service has an effect of 65.5% on customer satisfaction. While 34.5% customer satisfaction is influenced by other variables.